2021
DOI: 10.3389/fcvm.2021.710071
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Exposure–Effect Relationship Between Physical Activity and Incident Atrial Fibrillation in the General Population: A Dose–Response Meta-Analysis of 16 Prospective Studies

Abstract: Background: Since evidence regarding the relationship between physical activity (PA) and atrial fibrillation (AF) incidence is inconsistent among studies, we performed a dose–response meta-analysis to comprehensively evaluate the exposure–effect association between PA and incident AF and the potential sex difference in the general population.Methods: The PubMed and Embase databases were searched for eligible studies published up to July 2020 (PROSPERO: CRD42018091692). The non-linear or linear exposure–effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…A recent meta-analysis of 15 prospective studies, including 1,464,539 individuals, showed that PA engagement was associated with the decreased risk of AF 0.94 (0.90, 0.97) [ 8 ]. Another recent dose-response meta-analysis of 16 prospective studies, involving 1,449,017 individuals, showed that an increase of five metabolic equivalents of task-hour/week in PA was associated with the reduced risk of AF 0.992 (0.988, 0.996) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 15 prospective studies, including 1,464,539 individuals, showed that PA engagement was associated with the decreased risk of AF 0.94 (0.90, 0.97) [ 8 ]. Another recent dose-response meta-analysis of 16 prospective studies, involving 1,449,017 individuals, showed that an increase of five metabolic equivalents of task-hour/week in PA was associated with the reduced risk of AF 0.992 (0.988, 0.996) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through subgroup analysis, among participants with MUO, the modification of PA on AF risk was significantly higher in females than that in males. Wan et al showed that females reporting PA had lower AF incidence [43]. One possible mechanism was that the appropriate level of PA for males was higher than for females, while a high level of PA may decrease the modification of PA on the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It required at least two categories of coffee intake and the corresponding risk estimates with variance estimates. For these studies with no median or mean coffee intake level in each category, the midpoint of each category was estimated ( 21 , 22 ). If the highest or lowest category was open-ended, the open-ended interval length was assumed to be that of the adjacent interval ( 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%